Extended Precise Large Deviations of Random Sums in the Presence of END Structure and Consistent Variation. (8th March 2012) - Wang, Shijie; Wang, Wensheng
Abstract : The study of precise large deviations of random sums is an important topic in insurance and finance. In this paper, extended precise large deviations of random sums in the presence of END structure and consistent variation are investigated. The obtained results extend those of Chen and Zhang (2007) and Chen et al. (2011). As an application, precise large deviations of the prospective- loss process of a quasirenewal model are considered.